1992
DOI: 10.21273/horttech.2.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Irrigation at Container Nurseries

Abstract: Efficient usage of current water supplies is of great concern to container-nursery producers. Improving water management first requires knowledge of current commercial container production practices. In this study, irrigation distribution from overhead sprinklers was monitored at container nurseries to determine the distribution and the amount of irrigation applied during a typical irrigation cycle. Several nurseries surveyed had poorly designed irrigation systems; subsequently, irrigation distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 2 publications
2
20
0
Order By: Relevance
“…It means that two-fold increase of irrigation rate (from 12.5 to 25 mm in 2011 and from 25 to 50 mm in 2012) resulted in 2.75-and 2.23-fold (respectively in 2011 and 2012) increase in the amount of water leakage to the soil environment. The lower runoff volumes resulting from lower irrigation rates in this study are consistent with results reported by Fare et al (1992), Warsaw et al (2009a, b) and Sammons and Struve (2010). An efficient alternative to the standard practice of overhead irrigation can also be cyclic irrigation.…”
Section: Nitrate and Phosphate In Leachatesupporting
confidence: 93%
See 1 more Smart Citation
“…It means that two-fold increase of irrigation rate (from 12.5 to 25 mm in 2011 and from 25 to 50 mm in 2012) resulted in 2.75-and 2.23-fold (respectively in 2011 and 2012) increase in the amount of water leakage to the soil environment. The lower runoff volumes resulting from lower irrigation rates in this study are consistent with results reported by Fare et al (1992), Warsaw et al (2009a, b) and Sammons and Struve (2010). An efficient alternative to the standard practice of overhead irrigation can also be cyclic irrigation.…”
Section: Nitrate and Phosphate In Leachatesupporting
confidence: 93%
“…However, 22 B. Matysiak ____________________________________________________________________________________________________________________ such a system is easy to over-applicate water because it does not react to daily changes in precipitation or evapotranspiration and concomitant fertilizer and pesticide leaching. Existing irrigation estimates for container nursery production are as high as 2900 mm annually with as much as 33 mm daily (Fare et al 1992;Beeson & Brooks 2008). With overhead irrigation, the percentage of irrigation water that is intercepted by the plant/container ranges from 25% to 37%.…”
Section: Introductionmentioning
confidence: 99%
“…The need to improve irrigation practices and control runoff in container nurseries is well known. Fare et al (1992) found that irrigation volumes in container nurseries in Alabama varied greatly. Growers surveyed thought they were applying water at a rate of 2.54 cm · h -1 , but actual rates ranged from 0.8 to 3.2 cm · h -1 .…”
mentioning
confidence: 99%
“…Increased monitoring of irrigation applications is necessary to compensate for changing conditions in nurseries and to ensure irrigation is being applied uniformly and efficiently (Fare et al, 1992). Plant size has been found to be a determining factor in plant water use (Knox, 1989) and water use generally increases with plant age (Million et al, 2007).…”
mentioning
confidence: 99%
“…There has been limited development of these types of systems for field or container nurseries (Smajstrla and Koo, 1986). Field irrigation in the horticultural industry in many cases is based on a traditional rule of thumb; for example, watering plants 1 h a day (Fare et al, 1992). Manualcontrol or simple timers are sufficient to meet the needs of this type of watering system.…”
Section: Hypocotylsmentioning
confidence: 99%